State of Undergraduate Education in Emergency Medicine: A National Survey of Clerkship Directors. (January 2014) - Khandelwal, Sorabh; Way, David P.; Wald, David A.; Fisher, Jonathan; Ander, Douglas S.; Thibodeau, Lorraine; Manthey, David E.; Burton, John
Abstract Background The discipline of emergency medicine (EM) has rapidly changed over the past 10 years, resulting in greater involvement of the specialty in undergraduate medical education. Objectives The authors sought to present a review of how, when, and where EM is currently taught in U.S. medical schools and to include general program characteristics, such as number of required clerkships, clinical expectations and experiences, use of the national curriculum guide, didactic content, and methods of assessment and grading. Methods The authors surveyed representatives of the 128 U.S. allopathic medical schools on medical education in 2010. Contacts were drawn from established databases, direct inquiries, and medical school websites. Up to five attempts were made to contact representatives through e‐mail and telephone. Descriptive statistics were used to summarize the data. Results The survey response rate was 83.6%. Fifty‐two percent of medical schools now require students to complete EM clerkships. Required EM clerkships usually last 4 weeks and take place during the fourth year of medical school. They require students to complete a mean (±SD) of 14.3 (±2.8) shifts, which average 8.9 (±1.4) hours in length. Programs include a mean (±SD) of 18 (±10.4) hours of didactics. Approximately 60% of respondents report that both residents and attending physicians precept students. Assessments of students primarily include written clinical performance assessments and end‐of‐rotation written tests. These assessments contribute 66.8 and 24.5%, respectively, to the clerkship grade. Conclusions Currently more than half of all U.S. medical schools require EM clerkships in their undergraduate medical curricula. This article reports an overview of EM programs at the undergraduate level.